Molecular epidemiology of bovine leukemia virus in cattle and phylogenetic analysis for determining its prevailing genotype in Khyber Pukhtunkhwa, Pakistan - Farida Tahir; Umer Sadique; Farkhanda Tahir; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Shabana Naz; Rifat Ullah Khan; Naseer Khan Momand; Marco Ragni (Animal Biotechnology)
This research focused on assessing the molecular prevalence of Bovine Leukemia Virus (BLV) in different cattle farms throughout Khyber Pakhtunkhwa and characterizing the dominant BLV genotypes by analyzing partial sequences of the gp51 gene. A total of 1,250 blood samples were collected from cattle of both sexes, various age groups (<1 year, 1–3 years, 3–5 years, and >5 years), and different breeds (Friesian, Jersey, Sahiwal, Achai, and crossbred) from multiple cattle farms. Of the 1,250 samples tested, BLV was detected in 136 (10.88%) using nested PCR. Risk factor analysis revealed a significantly higher prevalence of BLV in exotic breeds and older cattle. To confirm the findings and genotype the BLV isolates, four PCR-positive samples were sequenced. Phylogenetic analysis identified the isolates as belonging to genotype I, closely related to GI BLV isolates from Japan. Furthermore, the isolates in this study formed a tightly clustered group, suggesting a common origin from an earlier virus introduced into the host population in the study area.